A cross‐sectional view of the current state of treatment of youth with type 2 diabetes in the USA: enrollment data from the Pediatric Diabetes Consortium Type 2 Diabetes Registry. Issue 3 (11th March 2016) - Nambam, Bimota; Silverstein, Janet; Cheng, Peiyao; Ruedy, Katrina J; Beck, Roy W; Paul Wadwa, R; Klingensmith, Georgeanna; Willi, Steven M; Wood, Jamie R; Bacha, Fida; Thomas, Inas H; Tamborlane, William V; et al.
Abstract : Objective: To describe the clinical characteristics, treatment approaches, clinical outcomes, and co‐morbidities of youth with type 2 diabetes (T2D) enrolled in the Pediatric Diabetes Consortium (PDC) T2D Registry. Methods: PDC enrolled 598 youth <21 yr of age with T2D from February 2012 to July 2015 at eight centers. Data were collected from medical records and interviews with participants and/or parents and included glycated hemoglobin (HbA1c), diabetes treatments, prevalence of diabetes comorbidities (hypertension (HTN), dyslipidemia (DL), microalbuminuria (MA), and nonalcoholic fatty liver disease (NAFLD). Results: Insulin use was observed in 45% of those with T2D duration <1 yr, 44% for 1–<2 yr, 55% for 2–3 yr and 60% for ≥4 yr. Median HbA1c was 6.7% (50 mmol/mol), 8.5% (69 mmol/mol), 9.6% (81 mmol/mol), and 9.7% (82 mmol/mol) in those with disease duration <1, 1–<2, 2–3 and ≥4 yr, respectively. Only 33 and 11% of those with HTN and DL respectively, were being treated. MA and NAFLD were observed in 5–6% of the participants. Prevalence of HTN was associated with higher BMI (p < 0.001), DL with higher HbA1c (p < 0.001), and MA with longer diabetes duration (p = 0.001). Conclusions: Frequency of insulin therapy in youth with T2D was associated with increased disease duration and those with longer duration rarely achieve target HbA1c level. This highlights the aggressive course of T2D in youth and adolescents. Additionally, co‐morbidities are not being adequately treated. Follow up data from the PDC will provide additional important information about the natural history of T2D and patterns of gaps in treatment.